Idiopathic Portal Hypertension. Issue 6 (29th November 2018) - Hernández‐Gea, Virginia; Baiges, Anna; Turon, Fanny; Garcia‐Pagán, Juan Carlos
Abstract : Idiopathic portal hypertension (IPH) is a rare disorder characterized by clinical portal hypertension in the absence of a recognizable cause such as cirrhosis. Laboratory tests often reveal a preserved liver function with anemia, leukopenia, and thrombocytopenia due to splenomegaly. Imaging studies reveal signs of portal hypertension, whereas liver stiffness and portal pressure values are usually normal or slightly elevated. Liver biopsy is considered mandatory in order to rule out other causes of portal hypertension, mainly cirrhosis. Liver histology may only show subtle or mild changes, and the definite diagnosis of IPH often requires an expert pathologist and a high‐quality specimen. The most frequent clinical presentation is variceal bleeding. Ascites is rarely observed initially, although it may occasionally appear during follow‐up. Typical histological findings associated with IPH have been described in patients without portal hypertension, probably representing early stages of the disease. Although the pathophysiology of this entity remains largely unknown, it is frequently associated with underlying immunological disorders, bacterial infections, trace metal poisoning, medications, liver circulatory disturbances, and thrombotic events. The long‐term prognosis of patients with IPH, where ascites and the underlying condition are important prognostic factors, is better than in patients with cirrhosis. Treatments that modify the natural history of the disease remain an unmet need, and management of IPH is frequently restricted to control of portal hypertension–related complications.